The munus in honour of Julia organized by Caesar: funerary ritual, social inequality and political interest in the republican Rome - López Medina, María Juana; Pérez Martínez, Francisco (ARYS. Antigüedad: Religiones y Sociedades, 2018)
This paper analyzes the munus of Julia offered by her father Caesar. It consists in the study of the figure of Julia, as daughter of Caesar and wife of Pompey, and the meaning that had her death. Her munus proves how the combats of gladiators, which were part of funerary rituals during the Republic, are an expression of social inequality, not only in function of the class also in relation to the gender, and how the munera are used by the political interests of the nobilitas, especially during the first century BC, as in this case.
Keywords: Munera gladiatoria; Rome; Julia; Caesar; Republic period; funeral rite; social inequality; political propaganda